UTILIZATION OF SWEET POTATO PEEL MEAL (Ipomoea batatas) IN THE DIETS OF RABBITS - Suleiman, U.; Abubakar, M.; Egbo, M.L. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The experiment was carried out at the Teaching and Research Farm of Abubakar Tafawa Balewa University (ATBU), Bauchi to evaluate the utilization of sweet potato peel meal (SPPM) as an energy source in the diets of growing rabbits. Twenty-four (24) growing rabbits with a mean initial weight ranging from 710.53 to 711.12 g were used for the eight (8) week study. The rabbits were randomly assigned to four treatments of six rabbits each, replicated three times in a completely randomized design (CRD). The experimental diets contained SPPM at levels of 0, 25, 50, and 75%, designated as Diets 1, 2, 3, and 4, respectively. Data were analyzed using one-way ANOVA, and means were separated using Tukey’s test at P<0.05. The results showed a significant differences (P<0.05) in final body weight, total weight gain (TWG), and daily weight gain (DWG), while feed intake and feed conversion ratio (FCR) were not significantly affected (P>0.05). Final body weight ranged from 1311.28 g (75% SPPM) to 1320.24 g (0% SPPM), TWG from 599.54 g (75% SPPM) to 609.13 g (0% SPPM), and DWG from 10.71 g (75% SPPM) to 10.87 g (0–25% SPPM). Daily feed intake ranged from 73.95 g to 76.83 g, total feed intake from 4141.06 g to 4302.90 g, and FCR from 6.80 to 7.06. Result of the carcass evaluation revealed a significant difference in carcass weight and dressing percentage. Carcass weights declined from 663.37 g (0% SPPM) to 652.68 g (75% SPPM), while dressing percentage dropped slightly from 50.24% to 49.77%. Hind limb and heart percentages also showed significant difference, whereas most other organ weights including liver, kidney, spleen, lungs, cecum, stomach, and intestines remained statistically similar across treatments (P>0.05). In conclusion, SPPM can be safely included in rabbit diets up to 50% for optimal growth performance, carcass yield, and organ development. It is recommended to incorporate SPPM at moderate levels as a sustainable and economical alternative energy source in rabbit production.